IN VITRO ALTERNARIA ALTERNATA EVALUATION OF BOTANICALS AGAINST INDUCING LEAF BLIGHT IN GROUNDNUT (Journal of Plant Disease Sciences, 2025)
Groundnut is a vital legume crop cultivated worldwide for its high oil and protein content, playing a significant role in food security and agro-industrial development, especially in India. However, its production is adversely affected by foliar diseases, particularly leaf blight caused by Alternaria alternata, which can lead to yield losses of up to 20%. This study aimed to evaluate the in vitro antifungal efficacy of seven botanicals — Allium sativum, Azadirachta indica, Zingiber officinale, Allium cepa, Curcuma longa, Datura stramonium, and Ocimum sanctum — against A. alternata using the poisoned food technique on potato dextrose agar (PDA). Aqueous extracts of the botanicals were tested at 15% and 20% concentrations. Results revealed significant suppression of mycelial growth by all botanicals compared to the control, with enhanced efficacy at the higher concentration. Zingiber officinale exhibited the strongest antifungal activity at both concentrations, achieving 92.21% inhibition at 20%, followed by Ocimum sanctum and Azadirachta indica. The study underscores the potential of plant-based extracts, particularly ginger, tulsi, and neem, as eco-friendly alternatives to chemical fungicides in managing leaf blight in groundnut. These findings contribute to sustainable disease management strategies aligned with environmental and food safety concerns.
Keywords: Alternaria; alternata; Efficacy; Leaf blight; Groundnut; Plant extracts